Pengaruh Model Pembelajaran Kooperatif Team Games Tournament (TGT) Berbantuan Media Teka–Teki Silang (TTS) Terhadap Hasil Belajar Dan Motivasi Siswa Pada Materi Tata Nama Senyawa Di Kelas X SMA Swasta Parulian 1 Medan - Agus Martinus Waruwu; Nora Susanti (Universitas Negeri Medan, 2019)
This study aims to determine student learning outcomes with the cooperative learning model TGT assisted by crossword puzzles on compound nomenclature material. Learning outcomes data collection tool used objective tests totaling 20 questions that have been tested for validity, difficulty level, different power, and reliability with an r value of 0.92. The results of data analysis showed an increase in student learning outcomes in the experimental class by 81.66% higher when compared to the control class by 75%. The average value of learning outcomes in the experimental class was 81.66 ± 9.17, while the average value of student learning outcomes in the control class was 75 ± 8.88. The results of the one-tailed t test were obtained tcount> t table (3.29> 1.67) so that Ha was accepted. This means that the learning outcomes of students in the experimental class are higher than those of the control class. The sum of students' motivation in the experimental class is initial motivation of 86.8, while final motivation is 96. This shows that the Team Games Tournament (TGT) cooperative learning model assisted by crossword media can improve learning outcomes and student motivation, and make a positive contribution to learning outcomes.